2022
DOI: 10.1002/asia.202200204
|View full text |Cite
|
Sign up to set email alerts
|

A pH‐Based Single‐Sensor Array for Discriminating Metal Ions in Water

Abstract: Human activities, such as mining and manufacturing, expose society and the natural environment to harmful levels of metal ions. Recently, optical sensor arrays for metal ion detection have become popular owing to their favourable features, such as facile sample preparation and the requirement of less expensive instrumentation compared to traditional, spectrometry‐based analysis techniques. Sensor arrays usually consist of numerous optical probes that are used in combination to generate unique analyte responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…[67] Following the similar strategy, New's group reported 7-hydroxy-4-methylcoumarin substituted with dipicolylamine moiety as a single-sensing element to discriminate among transition metal ions varying the pH. [68] A major challenge for the detection of analytes with the non-selective sensor is restricted by the intensive chemical synthesis and the associated cost of multiple sensing units required to generate a large number of data such that unique fingerprints for each analyte are obtained from the data set. To address the problem, photochromic receptors have been employed where the sensing element can generate two distinct outputs on photoisomerization.…”
Section: Selection Of Sensing Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…[67] Following the similar strategy, New's group reported 7-hydroxy-4-methylcoumarin substituted with dipicolylamine moiety as a single-sensing element to discriminate among transition metal ions varying the pH. [68] A major challenge for the detection of analytes with the non-selective sensor is restricted by the intensive chemical synthesis and the associated cost of multiple sensing units required to generate a large number of data such that unique fingerprints for each analyte are obtained from the data set. To address the problem, photochromic receptors have been employed where the sensing element can generate two distinct outputs on photoisomerization.…”
Section: Selection Of Sensing Elementsmentioning
confidence: 99%
“…A simplified yet fascinating natural fluorophore as the sensing element was reported from our group, where a single sensing element, curcumin, that can exist in two different forms on pH variation was demonstrated for discrimination among fourteen different lanthanide ions using machine learning techniques [67] . Following the similar strategy, New's group reported 7‐hydroxy‐4‐methylcoumarin substituted with dipicolylamine moiety as a single‐sensing element to discriminate among transition metal ions varying the pH [68] …”
Section: Selection Of Sensing Elementsmentioning
confidence: 99%
“…The concentration is lower or at least comparable to some of previous reports. [46,47] Furthermore, hierarchical cluster analysis (HCA) was carried out to classify multiple metals. The cluster tree yielded by HCA further confirmed that the sensor array could well distinguish 14 metal ions (Figure 2d).…”
Section: Identification Of Different Metal Ionsmentioning
confidence: 99%
“…Based on the inherent cross-reactivities of artificial receptors (Gardner, 1991), chemosensors in an array display a fingerprint-like response pattern according to the different types of analytes and their concentrations (Anzenbacher et al, 2010;Sasaki et al, 2021a). Therefore, qualitative and quantitative chemical information at the molecular level can be analyzed by data processing of the optical fingerprint-like response pattern (Huang et al, 2013;Sener et al, 2014;Xu et al, 2014;Hwang et al, 2015), allowing for accurate sensing, even in real samples (Palacios et al, 2008;Bowyer et al, 2022).…”
Section: Introductionmentioning
confidence: 99%